PENERAPAN METODE PEMBIASAAN OLEH ORANG TUA DALAM PEMBINAAN AKHLAK REMAJA - Hamida Hamida (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2014)
This study uses a qualitative approach and the type of descriptive research. Data collection techniques using interviews, observation and documentation. The techniques used are: data reduction, data display, and conclusion. 1) The results of the study show that: The role of parents in moral development through habituation applied by parents is to provide examples, invite teenagers and directly practice good behavior for teenagers and always give advice when teenagers make mistakes 2) The results of the application of the habituation method by parents in the formation of adolescent morals are that parents successfully apply the habituation method in fostering adolescent morals.